Gastrointestinal nematodes of Paramelomys platyops (Rodentia: Muridae) from Papua Indonesia and Papua New Guinea with the descriptions of a new genus and five new species of Heligmonellidae (Nematoda: Trichostrongylina) and a key to the species of Hughjonestrongylus - Smales, Lesley (Zootaxa, 2019)
Nematodes from six families, comprising 20 species identified to genus level and three to subfamily level as well as juveniles and a heligmonellid that could not be identified further, were recovered from 34 individuals of Paramelomys platyops, one P. cf playops and one Melomys sp. (Muridae: Murinae: Uromys Division) from Papua Indonesia and Papua New Guinea. Ascaridid larvae, a capillariid, Capillaria s. l., two putative species of the Nippostrongylinae and a small number of heligmonellid males and females, could not be identified further. The rictulariid Pterygodermatites sp. (females only) had not been reported previously from Sahulan Old Endemic fauna while three species, the oxyurid Syphacia longecauda , the molineid Hepatojarakus pyknofasciatus, and the spirurid Protospirura kaindiensis, had. The remaining species, all heligmonellids, included the brevistriatine Macrostrongylus ingens and 14 nippostrongyline species. Of these, Hughjonestrongylus amplicauda, H. singauwaensis, Melomystrongylus sepikensis, Mawsonema mokwanense, Odilia mackerrasae and Parasabanema szalayi had been reported previously. Species of Hasanuddina, Montistrongylus and Sanduanensis possibly as yet undescribed, could not be identified further. Flannerystrongylus abulus n. gen., n. sp. differed from all 41 genera described to date in having a synlophe of 14–16 evenly sized ridges with a sub frontal orientation. Hasegawanema yuroense n. sp. with 21–23 synlophe ridges was distinguished from its congeners by a combination of characters including length of spicule, cuticularisation of the genital cone, the proportions of the ovejector and the size of the eggs. Hughjonestrongylus pervulgatus n. sp., H. vanimoensis n. sp. and H. wanumaensis n. sp. were distinguished from all other species of Hughjonestrongylus and each other by a combination of characters including the number of synlophe ridges 25–30, 18, 22–23 in the mid body respectively, and spicule length, proportions of the ovejector and shape of the female tail. A key to the species of Hughjonestrongylus is provided. Species richness was greater than that recorded for P. lorentzii and P. rubex with about 86% of possible species found, as indicated by bootstrap analysis. The helminth assemblage was dominated by heligmonellids with eight species being unique to P. platyops. Paramelomys lorentzii is found at altitudes up to 1500 m and may provide a link between the lowland P. platyops and the highland P. rubex, thus facilitating the distribution of helminth species held in common.